Using Pde Mathematical Model For Airodynamics Of Lifting Surfaces In Non-Uniform Motion - M.Revathy,R.Anandhi, S.Manimekalai S.Gokilamani (International Journal of Scientific Research and Management (IJSRM), 2015)
The main scope of this paper is to solve the Boundary value problems in airodynamics of lifting surfaces in non-uniform motion by using application of Partial differential equation. The known volume element reserved in to problem to solve the unknown aerodynamic parameters by partial differential equations. In earlier days these kinds of problems are solved by trial and error method. Using of Partial differential equation to obtain the results is very close to exact values.